Organização de arquivos escolares: estudos sobre o arquivo da Escola Thomé de Medeiros Raposo - Lopes, Ilza Mara Pinheiro (Brasil, 2023)
Over the years, archives have gained space due to the great importance in keeping the memory and culture of society. They came from the Ancient Civilizations, but that brought relevance to the present day. The archives can be considered as a set of documents created or received by an organization, firm or individual, which keeps them in order as an information source for the execution of its activities. The documents preserved by the archive can be of various types and on various media. In this work the school archives, especially the archive of the Thomé de Medeiros Raposo State School is the object of discussion. Studies of school archives must align some useful observations, especially for those who dedicate themselves or who want to dedicate themselves and contribute to the preservation of institutional educational memory. With this information, our purpose is to make a study about the school's archive mentioned and try to understand its functionality so that we can elaborate an organization plan in the activities carried out in the space, according to the rules and legislation. For this purpose, we used as data collection, an exploratory research method where we had a conversation with former employees of the institution and the management team, where they reported the activities and the period of operation of the archive. We also obtained information, observing the activities carried out at the institution and how the documents are assigned to it. From the study we observed that there is a need to organize the archive, as an institution standard is established, but it is necessary to apply methods to obtain an improvement and a more considerable and effective result to carry out the activities.